Investigação de infecção natural de flebotomíneos por Leishmania (Viannia), no sul do Brasil - Ranucci, Thais Regina (2013)
Leishmaniasis is widespread in the world and has a significant impact on public health. The life cycle of Leishmania involves sand fly vectors and mammalian reservoirs that sustain it in rural and urban areas. The Multiplex Polymerase Chain Reaction (multiplex PCR) is a technique with high specificity and sensitivity that has been useful for detecting the presence of Leishmania in sand flies. The objective of this study was to investigate the natural infection of sand flies by Leishmania in Bandeirantes Municipality, Parana State. Two pairs of primers were used for multiplex PCR: i) the MP3H and MP1L to amplify a fragment of 70 pb of the conserved region from the minicircle of the kinetoplast of the subgenus Leishmania (Viannia), and ii) the 5Llcac and 3Llca to amplify a fragment of 220 pb from the IVS6 gene region of the cacophony in insects of the genus Lutzomyia, for internal control of the reaction. Were identified 737 sand flies female, of which 640 (66 pools) were tested by multiplex PCR. Were identified specimens of Pintomyia pessoai, Nyssomyia whitmani, Pintomyia fischeri, Nyssomyia neivai, Migonemyia migonei, Expapillata firmatoi e Brumptomyia brumpti. All pools showed the 220 bp fragment for sand flies DNA detection but were not found anyone with Leishmania infection. The multiplex PCR containing an internal amplification control has proved effective for detecting Leishmania infection in sand flies. Despite not having been detected the presence of Leishmania in analyzed sandflies, can not be denied the importance of Pi. pessoai, Ny. whitmani, Pi. fischeri and Ny. neivai in LT epidemiology, since these species have been found with natural infection in other studies. The population density, geographic distribution, domicile and peridomicile frequency, anthropophily, adaptation of these insects in anthropic environments and climatic conditions are favorable factors to the persistence of enzootic cycle of Leishmania. These factors highlight the need for research on sand flies behavior, including the infection rate, such results can be an indicator of the need for intervention by public health services, triggering measures of these insects' population control.